2018
DOI: 10.1002/jsfa.9125
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic activities of volatiles produced by two Bacillus strains against Monilinia fructicola in peach fruit

Abstract: These results indicate that the two antagonistic bacteria and some volatiles produced by them have potential value in controlling brown rot in harvested peach fruit. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…The multiple functions of 2-pentylfuran have also been identified. 2-Pentylfuran isolated from the volatile products of bacterial strains presented strong inhibition on both mycelial growth and conidia germination of F. oxysporum (Wu et al, 2015;Liu et al, 2018). 2-Pentylfuran fumigated from Bacillus megaterium strain XTBG34 could significantly promote plant growth of Arabidopsis thaliana (Zou et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multiple functions of 2-pentylfuran have also been identified. 2-Pentylfuran isolated from the volatile products of bacterial strains presented strong inhibition on both mycelial growth and conidia germination of F. oxysporum (Wu et al, 2015;Liu et al, 2018). 2-Pentylfuran fumigated from Bacillus megaterium strain XTBG34 could significantly promote plant growth of Arabidopsis thaliana (Zou et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…6-Methyl-2-heptanone produced by B. subtilis completely inhibited mycelial growth of F. oxysporum f. sp. lactucae (Liu et al, 2018). Acetophenone released by Streptomyces globisporus and Paenibacillus polymyxa can inhibit Penicillium italicum and F. oxysporum growth, respectively (Li et al, 2010;Raza et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The tenacious attachment, along with the secretion of extracellular lytic enzymes of two antagonistic yeasts (Pichia Alternaria alternata; endophyte bacteria; antifungal antagonism; cyclic lipopeptides; biological control membranefaciens and Cryptococcus albidus), may play a role in the biocontrol activity of yeast antagonists, and the interaction between yeasts and pathogens was hampered by a protein denaturant at low concentrations [10]. Bacillus strains have also been used to control Monilinia fructicola in peach fruit through the activity of volatiles released by the biocontrol strain [11]. Microbial antagonists have also been shown to be able to manage anthracnose in fruits [12].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that bacteria are an important reason for food spoilage and degradation [16,17,18,19,20]. To prolong the shelf life of the V. volvacea fruit bodies, this study focused on the bacterial community succession process on the surfaces of postharvest fruit bodies of V. volvacea and aimed to find a solution for V. volvacea fruit body preservation.…”
Section: Introductionmentioning
confidence: 99%